"The law was actually drafted by us but the Government is to be congratulated on its wise actions": British American Tobacco and public policy in Kenya. (12th February 2007) - Patel, Preeti; Collin, Jeff; Gilmore, Anna B
Abstract : Background and objective: British American Tobacco (BAT) has historically enjoyed a monopoly position in Kenya. Analysis of recent tobacco control debates and a case study of BAT's response to the emergence of competition in Kenya are used to explore the company's ability to shape public policy and its treatment of tobacco farmers. Design: Analysis of internal industry documents from BAT's Guildford depository, other relevant data and interviews with key informants. Results: BAT enjoys extensive high-level political connections in Kenya, including close relationships with successive Kenyan presidents. Such links seems to have been used to influence public policy. Health legislation has been diluted and delayed, and when a competitor emerged in the market, BAT used its contacts to have the government pass legislation drafted by BAT that compelled farmers to sell tobacco to BAT rather than to its competitor. BAT was already paying farmers less than any other African leaf-growing company, and the legislation entrenched poor pay and a quasi-feudal relationship. BAT's public relation's response to the threat of competition and the ministers' public statements extolling the economic importance of tobacco growing suggest that BAT has manipulated tobacco farming as a political issue. Conclusions: The extent of BAT's influence over public policy is consistent with the observations that, despite ratifying the Framework Convention on Tobacco Control, progress in implementing tobacco control measures in Kenya has been limited. The benefits of tobacco farming seem to be deliberately exaggerated, and an analysis of its true cost benefits is urgently needed. Tobacco farmers must be protected against BAT's predatory practices and fully informed about its activities to help them have an informed role in policy debates. As image, particularly around the importance of tobacco farming, seems key to BAT's ability to influence policy, the truth about its treatment of farmers must be publicised.